2020
DOI: 10.17712/nsj.2020.2.20190109
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes following intracranial haemorrhage: a retrospective cohort study

Abstract: Objectives: To improve the understanding of the association between electrocardiographic)ECG(abnormalities and clinical outcomes of patients with all types of intracranial hemorrhage)ICH(. Methods: A retrospective cohort study was conducted in a tertiary healthcare hospital on patients with ICH without cardiac disease or renal disease requiring dialysis. Demographic and clinical data were collected from hospital records. ECG record were Original Article obtained within 24 hours of presentation and prior to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Contrary to what occurred in the present case, previous research reported that death in patients with IPH was more common in cases in which changes in the ST segment were not observed (2).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to what occurred in the present case, previous research reported that death in patients with IPH was more common in cases in which changes in the ST segment were not observed (2).…”
Section: Discussioncontrasting
confidence: 99%
“…As observed in the present case, nontraumatic IPH results from small artery bleeding, commonly due to hypertension (15,16), and it generally occurs in patients older than 60 years of age (16). Previously, Yaghmoor et al (2) reported an IPH prevalence of 23% among all ICHs.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations